Gasteruption youngi sp. nov. (Hymenoptera: Evanioidea: Gasteruptiidae)from South Australia; an unusual species with trichoid sensilla on the ovipositor sheaths - Jennings, John T.; Parslow, Ben (Zootaxa, 2014)
Gasteruption youngi, sp. nov. (Evanioidea: Gasteruptiidae) is described based on several female specimens from South Australia. The new species is unusual in that it has stout trichoid sensilla on the ovipositor sheaths and long, thin trichoid sensilla on metasomal tergites T3–T8. The likely host is the colletid bee Euryglossula microdonta (Rayment, 1934).